Giant cell arteritis in Finland from 2010 to 2020: incidence, developing diagnostic methods and disease presentation - Kivitalo, Lauri; Taimen, Kirsi; Sokka-Isler, Tuulikki; Kerola, Anne; Rautavaara, Joonas; Pirilä, Laura; Kauppi, Markku; Malila, Joel; Haara, Laura; Ryyppö, Laura; Kotijärvi, Taina; Saarenketo, Panu; et al. (Oxford University Press (OUP), 2025)
Objectives
To study the annual incidence, diagnostic methods used and clinical presentation of giant cell arteritis (GCA) over time in Finland.
Methods
Newly diagnosed GCA patients from 2010 to 2020 were retrospectively identified from four healthcare districts in Finland. Medical records were reviewed and data on incidence, diagnostic methods, phenotype [cranial vs large vessel (LV)-GCA] and clinical presentation were analysed.
Results
We identified 602 newly diagnosed GCA patients. The annual incidence was 9.0 cases/100 000 persons (95% CI 8.3, 9.7) ≥50 years of age and was significantly higher in the period 2016–2020 compared with the period 2010–2015 [11.3 (95% CI 10.1, 12.5) vs 7.0 (95% CI 6.2, 7.9), P < 0.001]. Imaging- or biopsy-confirmed diagnosis was recorded in 75% of GCA patients, while 25% had a clinical diagnosis. The proportion of imaging- or biopsy-confirmed diagnoses increased over time [64.7% (2010–2015) vs 82.2% (2016–2020)] while that of clinical diagnoses decreased. The use of imaging methods increased while the use of temporal artery biopsies decreased between the two time periods. LV-GCA was discovered more often in the period 2016–2020 when compared with 2010–2015 (34.0% vs 19.3% of patients).
Conclusion
The incidence of GCA increased during the study period, as well as the proportion of imaging- or biopsy-confirmed diagnoses, probably due to more frequent use of advanced imaging methods. Additionally, patients with LV-GCA were more commonly identified.